Research on Multidimensional Interactive Teaching Mode of Ideological and Political Theory Course for Physical Education Majors in the University Based on Visual Communication Technology - Song, Peng; Wang, Shaojie; Jiang, Bo; Zhao, Lunan (Quality in Sport, 2024)
In traditional teaching concepts, teachers are regarded as the owners, transmitters and authorities of knowledge. With the arrival of the information age, the channels for students of sports major to know more about information have increased, and the concept of equality based on people in modern education has opened up a new situation of equal dialogue and exchange. The biggest difference between multi-dimensional interactive teaching mode and traditional teaching mode lies in its emphasis on interactivity and participation. Through purposeful communication and benign interaction teaching methods, combined with the characteristics of sports majors.In the process of teaching ideological and political theory, the abstract and boring theoretical knowledge is combined with the limited social experience of students of sports major to give students of sports major a new feeling, new experience and new stimulation. This kind of interactive and cooperative teaching activities has increased the appeal, persuasiveness and appeal of theoretical propaganda. Form an interactive space for multi-directional communication of teaching information, so that knowledge learning and ability development are unified. The use of visual communication technology in multi-dimensional interactive teaching fully mobilizes students of sports major’ enthusiasm, fun, intuitiveness and thinking, creating a passionate classroom teaching atmosphere.